Busted. (Economist, 1999)
Concentrates on the United States antitrust trial against Microsoft Corp. View that the defense of Microsoft lawyers was ineffective; Bill Gates as the designer of the defense; The belief that if Microsoft had admitted regret, it may have enabled a settlement; Impact of electronic mail messages that undermined Microsoft witnesses and supported government witnesses; Impact of the Windows operating system on software developers.